2015
DOI: 10.1007/s10265-015-0710-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Arabidopsis thaliana NRT1/PTR FAMILY (NPF) proteins capable of transporting plant hormones

Abstract: NRT1/PTR FAMILY (NPF) proteins were originally identified as nitrate or di/tri-peptide transporters. Recent studies revealed that this transporter family also transports the plant hormones auxin (indole-3-acetic acid), abscisic acid (ABA), and gibberellin (GA), as well as secondary metabolites (glucosinolates). We developed modified yeast two-hybrid systems with receptor complexes for GA and jasmonoyl-isoleucine (JA-Ile), to detect GA and JA-Ile transport activities of proteins expressed in the yeast cells. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
204
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(211 citation statements)
references
References 42 publications
5
204
2
Order By: Relevance
“…Although NRT2 transporters appear to be specific for nitrate, many NPF proteins transport substrates other than, or in addition to, nitrate. 18,19 Nonetheless, there are many different ways nitrate can enter an Arabidopsis cell. Expression of characterized transporters in Arabidopsis is restricted to specific cells and tissues, allowing the plant fine control over nitrate movement both into and within the plant.…”
Section: Nitrate and Aba In Root Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NRT2 transporters appear to be specific for nitrate, many NPF proteins transport substrates other than, or in addition to, nitrate. 18,19 Nonetheless, there are many different ways nitrate can enter an Arabidopsis cell. Expression of characterized transporters in Arabidopsis is restricted to specific cells and tissues, allowing the plant fine control over nitrate movement both into and within the plant.…”
Section: Nitrate and Aba In Root Developmentmentioning
confidence: 99%
“…Recently, several ABA transporters have been identified, many of which also transport other substrates. 19,[47][48][49][50] Increasing the concentration of one substrate is likely to have effects on the transport of the others. For AtNPF4.1, transport of the gibberellin, GA 3 , competes with ABA transport.…”
Section: Some Insightsmentioning
confidence: 99%
“…Plant hormones are active in plant tissues at very low concentration; therefore the synthesis, transport and signaling of hormones are precisely controlled processes (Chiba et al, 2015). Recent studies suggest that GA movement and distribution might be regulated by a group of GA transporters (Chiba et al, 2015;Saito et al, 2015).…”
Section: Tem Affects Palisade Mesophyll Development and Ga Transport mentioning
confidence: 99%
“…Recent studies suggest that GA movement and distribution might be regulated by a group of GA transporters (Chiba et al, 2015;Saito et al, 2015). The NITRATE TRANSPORTER 1/PEPTIDE TRANSPORTER FAMILY (NPF) is a family of proteins initially identified as nitrate or peptide transporters (Tsay et al, 2007;Léran et al, 2014), and was later found to also transport hormones such as auxin and abcisic acid (Krouk et al, 2010;Kanno et al, 2012).…”
Section: Tem Affects Palisade Mesophyll Development and Ga Transport mentioning
confidence: 99%
“…9 Recently, biochemical studies in heterologous systems allowed the identification of several GA transporters, belonging to the NITRATE TRANSPORTER 1/PEPTIDE TRANSPORTER FAMILY (NPF). [15][16][17] The NPFs represent a large family of membrane proteins which transport a wide array of compounds including nitrate, peptides, glucosinolates and phytohormones. 18 Although not demonstrated, it is tempting to speculate that these multifunctional transporters may contribute in the translocation of GA 12 from parenchyma cells to the vessels.…”
Section: Article Addendummentioning
confidence: 99%